Stretchable and durable conductive fabric for ultrahigh performance electromagnetic interference shielding. (April 2019) - Jia, Li-Chuan; Xu, Ling; Ren, Fang; Ren, Peng-Gang; Yan, Ding-Xiang; Li, Zhong-Ming
Abstract: Ultrahigh performance electromagnetic interference (EMI) shielding materials with an EMI shielding effectiveness (EMI SE) of above 90 dB at a tiny thickness are urgently needed due to the rapid development of high precision and sensitive electronic instruments. Herein, a highly electrically conductive fabric (ECF) was fabricated for ultrahigh performance EMI shielding by integrating silver nanowires (AgNWs) and conformal polyurethane (PU) layers on a carbon fiber fabric (CFF). The resultant ECF exhibited a very high electrical conductivity of 15390 S/m and an exceptional EMI SE of 106.0 dB at a thickness of only 0.36 mm. Importantly, the ultrahigh EMI SE was reliable in our ECF even undergoing long-term cycling deformations, with 83% retention after 100 stretching-release cycles (10% strain) and 97% retention after 5000 bending-release cycles (2.0 mm bending radius). The ECF also exhibited excellent resistance to ultrasonic treatment (60 min), peeling test (100 cycles), and strong acidic/alkaline solutions (PH = 2.0/12.0), indicating mechanical fastness and chemical durability. Our work demonstrates the facile development of an ultrahigh EMI shielding material with both mechanical and chemical durability, potentially suitable for high precision and sensitive electronic instruments even under harsh conditions. Graphical abstract: Image 1